Synthesis of Maltodextrin from Comercial Corn Starch with Variation of Alpha Amylase Concentration, Temperature and Hydrolisis Period for Determining Dextrose Equivalen Value - Fathoni, Rif'an; Zahratunnisa, Zahratunnisa (Jurnal Chemurgy, 2023)
Maltodextrin is defined as a partial starch hydrolysis product prepared by the addition of an acid or an enzyme, which contains α-D-glucose units which are mostly bound by - (1,4) glycosidic bonds. Maltodextrin is usually described by DE (Dextrose Equivalent). The commercial use of starch is affected by the DE value. The greater DE value means the more percentage of starch that turns into reducing sugars. This research was conducted by testing the DE value with maltodextrin production using alpha amylase enzyme catalyst by varying the enzyme concentration (0.2 ml; 0.4 ml; 0.6 ml), hydrolysis time (60 min; 90 min) and hydrolysis temperature (70°C ; 80°C). The results of the research give some point  that's the DE value obtained with the independent variables, which is  the time of hydrolysis and the concentration of the enzyme catalyst, experienced data fluctuations because the sample still had a lot of water. Also the higher of hydrolysis temperature, the greater DE value of maltodextrin was obtained.